DENDROBIUM ORCHID PROPAGATION TECHNIQUES FOR PKK MOTHERS IN GAMPONG LAMREH L.T SUB-DISTRICT INGIN JAYA ACEH BESAR: TEKNIK PERBANYAKAN TANAMAN ANGGREK DENDROBIUMUNTUK IBU-IBU PKK GAMPONG LAMREH L.T KECAMATANINGIN JAYA ACEH BESAR - Novi Mailidarni; Juliawati; Jauhari; Ilya Puryani (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2024)
Orchidaceae is a flower that is favored by most women, in order to develop Aceh for the future, Nanggroe Aceh Darussalam programmed orchid plants as one of the main commodities of ornamental plants, because orchids have beauty in their flowers and have various forms that have their own charm.  Orchid seeds in Banda Aceh are generally obtained from cuttings, but for people who have commercialized orchid businesses, seeds are obtained by buying tissue culture results because the seeds are more guaranteed. In this activity, orchid propagation is carried out vegetatively, namely with saplings (keiki). Keiki propagation of Dendrobium orchids is very simple and inexpensive and quickly adapts to the new environment.  The practical use of planting media and husk charcoal for the propagation of Dendrobium orchids has proven results that can be seen from the emergence of seedlings left on the media.